Sertifikasi Indikasi Geografis Kopi: Pendekatan Studi Bibliometrik - Saragih, Veny Betsy; Barus, Riantri; Yanti, Chicka Willy; Anggraini, Syadza (Journal of Integrated Agribusiness, 2024)
Geographical indication certification of coffee is growing due to the demand for "specialty" coffee based on geographic origin. According to coffee lovers, the taste of coffee varies, depending on where the coffee is produced. As demand for geographic indication certified coffee increased, the research that related to this topic also developed. To find out the extent of research that has been carried out regarding the topic, this bibliometic research was conducted. The purpose of this research is to map research on geographical indication certification of coffee based on keywords and research titles so that gaps and novelties related to the topic are obtained. The type of research used is a quantitative descriptive method. The analysis used is bibliometric analysis with the Vosviewers software tool. Based on the analysis results, it was obtained from the network visualization mapping that there were 6 clusters originating from 3032 terms with 50 keywords that appeared at least 10 times. In research on geographical indication certification, the 3 most keywords that appeared were coffee, Indonesia, geographical indications. From the mapping visualization results, it is known that the latest research topics studied are signs, Arabica coffee, coffee farmers, factors, indicators, Indonesian coffee, Robusta coffee, quality, and West Java. The average publication related to these items was published in 2020-2021. From the results of the visualization mapping, the density of research topics related to coffee items in cluster 1, Indonesian items in cluster 4, and geographical indication items in cluster 2 have been widely researched, while topics in clusters 3, 5 and 6 have not yet been widely researched. These items are signs, coffee farmers, indicators, value, quality, coffee farmers, Robusta coffee, quality, and West Java.